Degree of Science, Technology and Society (STS) science course - Nour, Abdel Moneim Abdeen Mohamed (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify The degree of containment of issues scienc, Technology and Society (STS) in the curriculum of science in the basic level in Sudan, the study used a descriptive approach, the study analytical tool in the card content analysis, the study sample consisted of science books the basic level in Sudan , the promise of five books, the most important findings of the Study:  the study sample consisted of science books the basic level in Sudan , the promise of five books, the study used a descriptive approach, the study analytical tool in the card content analysis, the most important findings of the Study:1- The curriculum of science for grade fourth got in the basis of the issues of science, technology and society, the proportion of the containment (22,06%) estimation small.2- The curriculum of science for grades (five, six, seven, eight) in the basis of the issues of science, technology and society, the proportions of the containment (2.95%,17,64%, 0.99% and 6.25%), respectively, all of the estimation (very small). 3- the curriculum of science in the basic level in Sudan, got in the basis of science and technology issues and the society, the proportion of the containment (9,835%) estimation is very small.The study concluded that several of the recommendations, the most important: the use of science and technology issues and society as a tool to develop science curriculum, and training teachers of science used in the teaching of science in the Sudan.
Keywords: basic education stage; science; society; technology; students; science course